MANAGEMENT OF USED PLASTIC BOTTLES INTO DECORATIVE GARDENS FOR A MORE BEAUTIFUL VIEW AT PGRI 1 MLANDINGAN KINDERGARTEN SCHOOL, SITUBONDO DISTRICT - Wapa, Andi (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
Turning used plastic bottles into a decorative garden at PGRI 1 Mlandingan Kindergarten in Situbondo Regency is a creative way to reduce plastic waste and enhance the beauty of the environment. By utilizing used plastic bottles as the main material, the decorative garden can be created with a unique and attractive design. A systematic and participatory planning, implementation, and evaluation process can help increase the success of the activity and provide greater benefits to the school and the environment. Thus, turning used plastic bottles into a decorative garden can be an effort to minimize the problem of plastic waste and enhance the beauty of the environment.
Keywords: Botol Plastik Bekas; Taman Hias; Pemandangan Indah